Fact-checking platforms in Spanish. Features, organisation and method (Communication & Society, 2019)
Fact-checking has become one of the most relevant activities of recent years, as a result of the increase in the flow of fake news and of the ease to spread news through platforms such as social media. The goal of the research is to assess the task of fact-checking developed by initiatives that use Spanish as a vehicle for comparing inaccurate and false information. We carried out a case study of 19 international projects that use Spanish as the main language to materialise their fact-checking actions and the analysis of contents published aims at understanding where these companies develop their activities, how are them internally organized and which methods they use to translate the data obtained to the audience. Results show that most of fact-checking projects in Spanish –launched most of them in the period 2014-2016– remain active. In South America, these organizations have more weight. Most of them have a journalistic nature, although there is a large number of civic and independent projects. Among strategies for verification, text is the preferred formula, although some innovative methods to present the degree of accuracy of assessed contents have been found.